An Encounter with Simone Weil - Haslett, Julia (United States : Galvango, Fabrizia ; Grunning-Harris, Klara ; Cullen, Enrico Rossini, 2010)
An Encounter with Simone Weil tells the story of French philosopher, activist, and mystic, Simone Weil (1909-1943) -- a woman Albert Camus described as "the only great spirit of our time." On her quest to understand Simone Weil, filmmaker Julia Haslett confronts profound questions of moral responsibility both within her own family and the larger world. From the battlefields of the Spanish Civil War to anti-war protests in Washington DC, from intimate exchanges between the filmmaker and her older brother, who struggles with mental illness, to captivating interviews with people who knew Simone Weil, the film takes an unforgettable journey into the heart of what it means to be a compassionate human being.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films